Cultivating research interest among undergraduate students: Becoming a career physician-scientist - Jin, Shigeki; Takeuchi, Akiko; Murakami, Manabu (Journal of the Pakistan Medical Association, 2024)
Although the importance of scientific research is self-evident, there need to be more physician-scientists1. There is a concern regarding how research interest can be cultivated among undergraduate students. Ahmed et al.2 examined the factors that hinder students from pursuing undergraduate research and the proposed solutions. The authors’ latest research findings (not yet published) may enhance the generalizability of this study, considering data triangulation, with regard to increasing research-oriented physicians. In the aforementioned research, the authors interviewed 19 first-year students studying liberal arts and basic medicine and 12 third-year students studying clinical medicine. The interviews lasted 60 minutes per participant, and the recordings were transcribed, coded, and grouped for similarity in content. The interviews focused on factors that prevent students from pursuing a career as physician-scientists and how to address these factors. The following four factors were extracted: 1) Lack of recognition of the researcher’s image due to students’ inexperience; 2) Negative image of researchers (long, monotonous work, negative research results, and lack of work-life balance); 3) Intense research competition and employment instability; 4) Economic anxiety over low salaries and livelihood security. Notably, despite the different locations, methods, and persons being studied, these four factors are consistent with and explain the tree figure (main themes, along with subthemes) created by Ahmed et al.2 The students in the authors’ study also suggested countermeasures to improve these factors (See Table 1). Research on career guidance for physician-scientists has recently increased worldwide, and programs have been developed to support students aiming for research careers3. However, in many cases, these attempts do not succeed because of low motivation among students and concerns for their careers. Increasing students’ motivation to conduct research at an earlier stage has attracted attention as an effective method. Future studies must confirm whether sensitizing students toward research at an early stage is effective. If we fail to nurture and retain students with research-oriented mindsets, there is a risk of “brain drain,”4 which could have severe implications for future research productivity. Taking cues from a previous study that attempted to quantitatively examine the intrinsic or extrinsic motivation to increase the number of physician-scientists5, the authors attempted to qualitatively explore these factors in Japan, extending a similar study by Ahmed et al.2 in Pakistan. Effective measures for increasing the number of physician-scientists worldwide must be reported by future studies.